UFC-Inventor: um ambiente para modelagem e geração de aplicações para Aulas de Campo Ubíquas - Barros Filho, Edgar Marçal de (2016)
Field trips (or field classes) promote the scientific spirit of the students by increasing the ability of observation and discovery in various areas of knowledge. By incorporating ubiquitous technologies, such as sensors and actuators, in the field classes (here called Ubiquitous Field Classes), they show benefits when compared to traditional classes. However, the development of ubiquitous systems has challenges, such as seamless treatment of the devices heterogeneity; absence of fixed communication infrastructure; dynamics of the computational elements of the environment; and support for user mobility. In the literature review, we have not found a tool that enables modeling and generation of cross-platform applications for ubiquitous field classes aimed at teaching professionals with little or no knowledge of programming. This document presents a doctoral thesis that consists of a computational environment called the Ubiquitous Field Classes Inventor (UFC-Inventor), which comprises of a modeling language and integrated systems. Together, they enhance the use of ubiquitous technologies in field classes. Thus, teaching professionals can create graphical models of their field classes and, from it, generate cross-platform ubiquitous applications to be used by students. First, we conducted a systematic mapping study with articles on experiences on the use of ubiquitous technology in education. From this survey, we identified some important requirements for ubiquitous field classes. From them, we designed and implemented the UFC-Inventor and its components. The first component is the ML4UL (Modeling Language for Ubiquitous Learning), a domain specific language focused on representation of ubiquitous field classes through an open and reusable specification. The UFC-GLM module, indeed, allows graphic modeling of the field classes with ubiquitous computing resources. The third module is the UFC-Generator, which is responsible for generating the ubiquitous applications. We carried out an evaluation of UFC Inventor with five teachers aim at verifying the usability of the environment. Also, we implemented a case study in the field with seventeen students. The results of both evaluation experiments suggest the acceptance of the UFC-Inventor and indicate that its execution has occurred correctly.